HLA-matched living-related conjunctival limbal allograft for bilateral ocular surface disorders: long-term results - Scocco,Caio (2008)
PURPOSE: To evaluate the long-term outcome of HLA-matched lr-CLAL for bilateral ocular surface disorders. METHODS: A retrospective, non-comparative interventional case series study of 39 eyes of 32 patients with bilateral surface disorders and clinical diagnosis of limbal stem cell deficiency who underwent HLA-matched lr-CLAL. Visual acuity (VA), ambulatory vision (> 20/200) and ocular surface stability were evaluated as main outcomes. Donor limbus was obtained from a sibling or a parent of the patient, after an appropriate Class I and II HLA match. RESULTS: One year after surgery, VA improved in 46.2%, ambulatory vision was achieved in 48.7% and a stable corneal surface was achieved in 84.6% of the eyes. At the final follow-up (mean, 48.7 ± 30.6 months), 66.6% of the eyes that had gained VA one year after surgery maintained an improved VA (p=0.28), 94.7% of eyes that had achieved ambulatory vision one year after surgery maintained 20/200 or better (p<0.001) and 93.9% still had a stable corneal surface (p=0.043) at the final follow-up. CONCLUSIONS: HLA-matched lr-CLAL can be an adequate method of treatment for bilateral ocular surface disorders, with a reasonable percentage of success of long-term results.